Descriptions Of Aliens (Extraterrestrial Beings) In Vedic Scriptures - I.B. Arya Lawa Manuaba; I Nyoman Sudirman (Institut Hindu Dharma Negeri Denpasar, 2018)
Polemics emerge when religion is faced to the fact that there are supposedly visitation of intelligent beings from other planets in many cases from ancient times up to now. Vedic literature as basis of Hindu religious teachings is one of many religious resources which can be used as reference to this inquiry. This descriptive-qualitative study aims to (1) clarify whether Vedic Scriptures mention about extraterrestrial life, or intelligent life outside Planet Earth, and (2) enlist categories of extraterrestrial life as mentioned in the Vedic Scriptures. The methods used are literature study and documentary. Result of the study reveals that Vedic Scriptures, especially the four Vedas, Puranas and Itihasas clearly mention about existence of extraterrestrial species (alien beings) and their interactions with humans since the Vedic era. These extraterrestrial beings are of different categories which are more elaborately enlisted in some major Puranic literatures.